2014
DOI: 10.1586/17446651.2014.894877
|View full text |Cite|
|
Sign up to set email alerts
|

Metreleptin for metabolic disorders associated with generalized or partial lipodystrophy

Abstract: Lipodystrophy is a group of acquired and inherited disorders characterized by selective loss of adipose tissue. Despite wide genotypic and phenotypic variety, many patients with lipodystrophy have similar metabolic complications including insulin resistance, diabetes mellitus, hypertriglyceridemia and hepatic steatosis. Often, these metabolic abnormalities are severe and difficult to treat with conventional glucose and lipid-lowering therapies. Lack of adipose tissue also results in marked hypoleptinemia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Further, leptin has been used in lipodystrophic animals or patients, where low leptin levels were associated with hyperphagia and increase of fat storage in the liver and skeletal muscle, and finally to type II diabetes and metabolic disorders [115,116]. Leptin or metreleptin (the recombinant methionyl form of the human hormone) administration is able to improve glucose homeostasis and plasma lipid profile, and reduce steatosis in metabolic disorders associated with lipodystrophy or human virus-associated immunodeficiency [117,118]. In 2014, the U.S. Food and Drug Administration approved metreleptin, for injection, as replacement therapy to treat the complications of leptin deficiency, in addition to diet, in patients with congenital or acquired generalized lipodystrophy.…”
Section: Leptin In Therapy and Leptin Sensitizersmentioning
confidence: 99%
“…Further, leptin has been used in lipodystrophic animals or patients, where low leptin levels were associated with hyperphagia and increase of fat storage in the liver and skeletal muscle, and finally to type II diabetes and metabolic disorders [115,116]. Leptin or metreleptin (the recombinant methionyl form of the human hormone) administration is able to improve glucose homeostasis and plasma lipid profile, and reduce steatosis in metabolic disorders associated with lipodystrophy or human virus-associated immunodeficiency [117,118]. In 2014, the U.S. Food and Drug Administration approved metreleptin, for injection, as replacement therapy to treat the complications of leptin deficiency, in addition to diet, in patients with congenital or acquired generalized lipodystrophy.…”
Section: Leptin In Therapy and Leptin Sensitizersmentioning
confidence: 99%
“…Numerous animal models have shown that exogenous supplementation of leptin, in order to achieve physiological levels of the hormone, is effective in restoring normal glycemic control, normal serum lipid profile and liver function (10,11). In humans, leptin replacement therapy (LRT) with recombinant methionyl human leptin (r-metHuLeptin, metreleptin) has been evaluated by several clinical trials (12), and has been recently approved by the FDA for the treatment of patients with generalized lipodystrophy (13). Administered as a subcutaneous injection once or twice daily, metreleptin reverses the metabolic abnormalities that are seen in LS, leading to significant improvements in overall health (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Metreleptin is a protein of ≈ 16 kDa that differs from endogenous human leptin by having an amino-terminal methionine residue [5]. Being an analogue of human leptin [3,5], metreleptin binds to and activates the leptin receptor, thus mimicking the physiological effects of endogenous leptin [8]. Metreleptin improves metabolic abnormalities associated with LD, including glycaemic control, hypertriglyceridaemia and insulin sensitivity [5,9].…”
Section: How Does Metreleptin Work?mentioning
confidence: 99%
“…generalized LD) or only in specific areas (i.e. partial LD) [1], with abnormal accumulation of fat in unaffected regions often evident [3]. Fat tissue plays a key role in lipid metabolism and glucose homeostasis [4], and its loss in LD interferes with hunger/satiety signals (commonly leading to hyperphagia), resulting in inappropriate lipid storage in muscle, the liver and other organs [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation